Prison Letters of St. Ap. Paul: Theories about the Place of Writing - Boev, Georgi (Forum Theologicum Sardicense, 2025)
Georgi Boev, Prison Letters of St. Ap. Paul: Theories about the Place of Writing. In this article, I discuss three different theories regarding the location where Apostle Paul wrote the prison letters: Ephesians, Philippians, Colossians, and Philemon. These theories are widely debated among contemporary biblical scholars.